2018
DOI: 10.14260/jemds/2018/699
|View full text |Cite
|
Sign up to set email alerts
|

HRCT Temporal Bone- A Mandatory Preoperative Investigation for Improving Surgical Outcome in Unsafe Csom

Abstract: BACKGROUND Chronic Suppurative Otitis Media (CSOM) is considered to be a slowly progressive destructive disease of the middle ear. It is the most commonly encountered middle ear pathology, which disrupts the normal anatomy and physiological functioning of the ear. Otoscopic evaluation is sufficient to establish the diagnosis of the disease; however, its extent can be determined only on the basis of a High Resolution Computed Tomography (HRCT) of the temporal bone. While the most common presentation of CSOM is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
3
1
0
Order By: Relevance
“…This is comparable to the study by Sirigiri and Dwaraknath who found sensitivity of 100% and specificity of 94% [16]. The positive predictive value is low 66.6% which correlates with the study by Baviskar et al which was 66.7% [22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is comparable to the study by Sirigiri and Dwaraknath who found sensitivity of 100% and specificity of 94% [16]. The positive predictive value is low 66.6% which correlates with the study by Baviskar et al which was 66.7% [22].…”
Section: Discussionsupporting
confidence: 88%
“…HCRT is 100% sensitive and specific to detect scutum erosion which is in accordance with the study by Juveria and Sudarshan and Rocher et al [20,21]. The tegmen was found to be eroded in 12% of cases with sensitivity of 100% which is in accordance with Baviskar et al [22] and Jackler et al [15]. However, few studies have shown lower sensitivity values between 45 and 50% [9][10][11].…”
Section: Discussionsupporting
confidence: 87%
“…Erosion of the facial nerve canal was found in 32% cases in our study with the tympanic part being more commonly affected which is more than as observed by Baviskar S et [14] al in his descriptive study of 50 patients of unsafe CSOM.The variable results can be explained by the small number of cases of facial [10] nerve canal dehiscence and statement made by Mafee et al .They had stated that visualisation of thin bony structures like facial nerve canal may be misleading due to error in computer reconstruction of their images. The fact that computer averages their density with adjacent soft tissue and air makes these structures appear eroded.…”
Section: Facial Nerve Canal Erosionsupporting
confidence: 62%
“…Tegmen tympani erosion was seen in 38% cases in our study. In the study conducted by Baviskar [14] et al showed erosion of tegmen tympani only in 20% cases.…”
Section: Tegmen Tympani Erosionmentioning
confidence: 94%